2016
DOI: 10.1142/s0129183116501412
|View full text |Cite
|
Sign up to set email alerts
|

Model for the growth of the world airline network

Abstract: We propose a probabilistic growth model for transport networks which employs a balance between popularity of nodes and the physical distance between nodes. By comparing the degree of each node in the model network and the World Airline Network (WAN), we observe that the difference between the two is minimized for α ≈ 2. Interestingly, this is the value obtained for the node-node correlation function in the WAN. This suggests that our model explains quite well the growth of airline networks.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Failure, damage spread and recovery crucially underlie many spatially embedded networked systems ranging from transportation structures to the human body 1 2 3 4 . Advances in the study of networks have led to important progress in understanding resilience and controllability in terms of the interaction between topology and various underlying spreading dynamics 5 6 7 8 9 10 .…”
mentioning
confidence: 99%
“…Failure, damage spread and recovery crucially underlie many spatially embedded networked systems ranging from transportation structures to the human body 1 2 3 4 . Advances in the study of networks have led to important progress in understanding resilience and controllability in terms of the interaction between topology and various underlying spreading dynamics 5 6 7 8 9 10 .…”
mentioning
confidence: 99%
“…Nevertheless, the spatial patterns and the structure of these regions show that the current system of airline traffic is very heterogeneous and its description and analysis through quantitative methods (regionalisation, categorisation, identification of hierarchy) is not easy (Verma et al, 2016). This spatial organisation is affected by some relatively stable factors, such as the economic situation in a particular region and its tourist appeal, and it is also affected T A B L E 2 Size and categories of world airline hubs by some variable factors, such as the prevailing political situation.…”
Section: Discussionmentioning
confidence: 99%
“…A closer look at global air transport, using the concept of functional regions and with the help of a regionalisation algorithm, has identified 11 global FARs which are relatively autonomous in the world air transport system. Nevertheless, the spatial patterns and the structure of these regions show that the current system of airline traffic is very heterogeneous and its description and analysis through quantitative methods (regionalisation, categorisation, identification of hierarchy) is not easy (Verma et al, 2016). The FARs defined in this paper can be compared to other macro-scale regionalisations of the world (e.g., De Blij & Muller, 1997;Huntington, 1996, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Exploiting the natural sparsity of the vectors, the pioneering work has applied EEM to achieve a successful reconstruction in scale-free networks with a small fraction of hubs [25]. However, in many cases, examples of real-world networks are not characterized by scale-free [26], i.e., the collaboration network of film actors [27,28], the neural network of the worm Caenorhabditis elegans [26], the power grid of the western United States [29,30], and drug trafficking network [31], et al In addition, unique structure could be observed in world airline networks [32,33] and Apollonian networks [34][35][36], which are characterized by scale-free and also satisfies basic features of small-world. EEM for reconstructing networks characterized by other features has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%